An Overview of Disease and Parasitism in Southeastern Bobwhite Quail - William R. Davidson; Forest E. Kellogg (National Quail Symposium Proceedings, 2017)
(Invited Paper) Salient information on diseases and parasites of bobwhite quail (Colinus virginianus) in the southeastern United States is summarized. Major diagnostic findings on 146 bobwhites submitted to our regional wildlife disease laboratory from 1972 through 1981 included traumatic injuries, various toxicoses, and avian pox. Traumatic injuries were diagnosed frequently throughout the 10-year period, whereas toxicologic problems occurred sporadically. Avian pox emerged in outbreak proportions in the region in 1978 and thereafter has been prevalent in localized areas, Prompted by severe aflatoxin contamination in southeastern corn crops in 1977, studies on aflatoxicosis in bobwhites indicated that risks to wild bobwhite populations were minimal, Serologic, pathologic, and virus isolation studies disclosed infections of quail bronchitis virus and TR-59 adenovirus in bobwhites in northcentral Florida, Extensive studies have revealed only infrequent minor lesions associated with ectoparasites and endoparasites, and it was concluded that parasitism is not an important mortality factor in wild bobwhites, Two diseases encountered in pen-raised bobwhites, avian pox and histomoniasis (blackhead disease), clearly have potential to produce problems in wild bobwhites and wild turkey,